Efficacy and safety evaluation of HSD‐1 inhibitor ABT‐384 in Alzheimer's disease. (13th January 2014) - Marek, Gerard J.; Katz, David A.; Meier, Andreas; Greco, Nicholas; Zhang, Wuyan; Liu, Wei; Lenz, Robert A.
Abstract: Background: In this study we assessed increased cortisol in Alzheimer's disease (AD) patients. The selective 11‐β‐hydroxysteroid dehydrogenase type 1 (HSD‐1) inhibitor ABT‐384 blocked regeneration of active cortisol and this tests the hypothesis that intracellular hypercortisolism contributes to cognitive impairment. Methods: In this double‐blind, placebo‐ and active‐controlled phase II study we examine the efficacy and safety of ABT‐384 given 10 mg or 50 mg once daily, donepezil 10 mg once daily, or placebo for 12 weeks in subjects with mild‐to‐moderate AD. The primary efficacy end point was the change from baseline to final evaluation on the 13‐item Alzheimer's Disease Assessment Scale–Cognitive subscale (ADAS‐Cog) total score. Results: The study was terminated for futility after randomization of 267 subjects. ABT‐384 did not improve ADAS‐Cog scores or any secondary end point; however, donepezil significantly improved both cognition and functional end points. Overall incidence of adverse events was similar among treatment groups. Conclusion: ABT‐384, when tested at doses associated with complete brain HSD‐1 inhibition, did not produce symptomatic improvement in AD.